EVALUASI MUTU BERAS DAN TINGKAT KESESUAIAN PENANGANANNYA (STUDI KASUS DI KABUPATEN KARANGANYAR) - Alfina Handayani; Sriyanto Sriyanto; Ita Sulistyawati (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2013)
Rice is a major commodity in Indonesia. In the free trade era, the local rice should be able to compete with imported products. Consequently, the availability of rice not only in quantity but also consider the quality aspects. This study aims to analyze the quality of the rice and the handling compliance level in order to do the proper improvement measures. The results showed that 38 percent of the rice samples analyzed did not apropriate with SNI, 31 percent on the quality V, 15 percent in grade IV and 15 percent in the third quality. The highest handling level average was 78 percent in RMU and 67% in farmer, while the lowest of the rice supply chain was 39% in merchant.